Dissipation dynamics of clothianidin and its control efficacy against Bradysia odoriphaga Yang and Zhang in Chinese chive ecosystems. Issue 7 (17th November 2015) - Zhang, Peng; He, Min; Zhao, Yunhe; Ren, Yupeng; Wei, Yan; Mu, Wei; Liu, Feng
Abstract: BACKGROUND: Clothianidin is a second‐generation neonicotinoid insecticide that is quite effective against Bradysia odoriphaga Yang and Zhang, the major insect pest affecting Chinese chive in northern China. In this study, the dissipation of clothianidin in soil and its residue in leaves and pseudostems/bulbs as well as its control efficacy against B. odoriphaga and two other secondary pests were investigated in Chinese chive fields after soil application of clothianidin by the directional spray–washing method. RESULTS: The half‐life of clothianidin was 35.73–36.10 days, and it could be detected in Chinese chive plants in both treatment plots up to 240 days after a single soil application. Clothianidin applied at 3.0 and 6.0 kg AI ha −1 could suppress B. odoriphaga population growth, achieve satisfactory levels of pest control for almost 10 months and reduce the losses of the yield in winter. Moreover, the treatments also significantly reduced Thrips alliorum and Acrolepia alliella populations up to nearly 180 days after one application. CONCLUSION: Clothianidin can be considered to show long‐lasting efficacy against B. odoriphaga and to be safe for use in Chinese chive at 3.0 and 6.0 kg AI ha −1 once in the early root‐rearing period to control B. odoriphaga in these cultivation ecosystems. © 2015 Society of Chemical Industry